When tears become a language: Frictions in a xenophobic national 'imaginary'. Issue 1 (1st March 2017) - Hove, Muchativugwa
In the past few years, South Africa has experienced three widely publicized xenophobic attacks on foreign nationals. The victims of each of these incidents of antiimmigrant violence were Mozambican nationals and each received prominent media attention: the 'burning man' of 2008; the 'police-dragged' national of 2013; and the savagely-knifed Emmanuel Sithole of Alexandra in 2015. This article is framed by these incidents, in which the 'alien' found their negotiation of identity and history subverted by experiences in the diaspora. It discusses these incidents in order to broadly interrogate xenophobia, and in order to locate the genesis and implications of violent multicultural nuances reported in several hundred televisual broadcasts and newspaper articles across South Africa. A critical discourse analysis of these reports provides a platform for an examination of the nationalist and ethnicitycentred dynamics at play, and attempts to generate an understanding of the historical genesis of xenophobia in South Africa. Diasporic refugee and migrant movements within Southern Africa in recent times have brought about the 'right to narrate', hence the article's enquiry into narratives, sites, sights, media reports and witness accounts that cut across the narrower interests of polities and nation states.